2016
DOI: 10.1021/acs.est.5b04975
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 Population Exposure in New Delhi Using a Probabilistic Simulation Framework

Abstract: This paper presents a Geographical Information System (GIS) based probabilistic simulation framework to estimate PM2.5 population exposure in New Delhi, India. The framework integrates PM2.5 output from spatiotemporal LUR models and trip distribution data using a Gravity model based on zonal data for population, employment and enrollment in educational institutions. Time-activity patterns were derived from a survey of randomly sampled individuals (n = 1012) and in-vehicle exposure was estimated using microenvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…higher compared to static estimates in Dhondt et al (2012) and de Nazelle et al (2013),respectively. In another Asian city setting, Saraswat et al (2016) found ignoring effects of mobility led to an underestimation of annual PM2.5 population exposure by about 11% in New Delhi. When work locations were considered in addition to residential, exposures to NOX and NO2 were found to increase by 5 -10 ppb (Shafran-Nathan et al, 2017).…”
Section: Comparison To Other Studiesmentioning
confidence: 96%
See 3 more Smart Citations
“…higher compared to static estimates in Dhondt et al (2012) and de Nazelle et al (2013),respectively. In another Asian city setting, Saraswat et al (2016) found ignoring effects of mobility led to an underestimation of annual PM2.5 population exposure by about 11% in New Delhi. When work locations were considered in addition to residential, exposures to NOX and NO2 were found to increase by 5 -10 ppb (Shafran-Nathan et al, 2017).…”
Section: Comparison To Other Studiesmentioning
confidence: 96%
“…In other studies assessing dynamic air pollution exposure, mobility or time-activity data were derived from transport and activity-based simulation models (Setton et al, 2011;Dhondt et al, 2012), GPS (Dons et al, 2011), mobile-based tracking (de Nazelle et al, 2013), travel smartcard (Smith et al, 2016), travel surveys (Saraswat et al, 2016) or cellular network information (Dewulf et al, 2016;Nyhan et al, 2016). These were combined with air pollution modeling to assess personal and population exposure to pollutants.…”
Section: Comparison To Other Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in population demographics may also be important. A recent exposure modeling study for PM 2.5 in New Delhi focused on population mobility and transport-related exposures using a probabilistic framework that included a land use regression component and a zonal model to simulate home and work locations and commuting between them (Saraswat et al, 2016).…”
Section: Exposure Modellingmentioning
confidence: 99%